ANALISIS SEKTOR POTENSIAL DAN KETERKAITAN ANTAR WILAYAH PADA PEREKONOMIAN KABUPATEN OGAN KOMERING ULU (OKU) TAHUN 2010-2016 - Lisa Hermawati; Nopita Sari (STIE DWI SAKTI BATURAJA, 2018)
The purpose of this study is to find out what potential sectors need to be developed in OKU Regency and find out the relationship between OKU District and the surrounding Regencies/Cities to support its economic growth. The results of this study indicate that in the period 2010-2016, there are 9 potential sectors that need to be developed in OKU Regency, namely the Agriculture, Forestry and Fisheries Sector; Water Supply, Waste Management, Waste and Recycling Sector; Wholesale and Retail Trade Sector, Car and Motorcycle Repair; Sector of Providing Accommodation and Foods and Drinks; Financial Services and Insurance Sector; Real Estate Sector; Education Services Sector; Health Services Sector and Social Activities; Other service sectors. Based on gravity analysis, the Regency with the most interaction with OKU Regency is Muara Enim Regency and the weakest interaction is Ogan Ilir Regency. The connection of Muara Enim Regency and OKU Regency is the biggest because the two regions have a close enough distance so that the interaction of them is the strongest.